(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article presents an analysis of the research conducted among students of the faculty of psychology. The purpose is to study the place and role of the psychological service of the school (school psychologist) in the overall process of educational socialization of yesterday’s schoolchildren. The study involved 123 students. The geography of the schools where the respondents studied were extremely wide – from Kyiv to the small village of Novosilki (Kyiv, Poltava, Odessa, Khmelnytsky, Vinnytsia, Chernigov, Kropivnitsky, Cherkasy, Lugansk, Sumy, Belaya Tserkov, Kalush, Kremenchuk, Mariupol, Yanchenko-Podilsky, Ostrog, Pokrovsk, Hrebinka, Chervonograd, Zelenodolsk, Melnitsa-Podilsky, Terka and others). They were offered a questionnaire containing 10 questions, as well as a projective picture. The results show that the school psychologist takes most of the time to test (without legalizing goals and testing results). Often meetings with a psychologist are related to the issue of professional orientation, the choice of profession, diagnosis of professional abilities. The term "consultation" is not actually mentioned by the students. In 10.4% of respondents, negative emotions associated with a psychologist have been preserved, in particular, it indicates unprofessional actions: violation of confidentiality, moral pressure, humiliation against classmates. Lack of real interaction between students and a psychologist, more often it is formal. The students noticed that the psychologist had never had contact with parents, and 5 persons received professional out-of-school psychological assistance. Among the functions that were not specific to the psychologist was the replacement of the lessons of other teachers, the organization of holidays, or even in general. The psychologist at school has no autonomy, the subject of activity is "dissolved" in pedagogical activity, the functions and role that he performs negatively affects his professional identity. The obtained results give grounds to assert the necessity Modernization of the system of school psychological service taking into account transformational changes in the school environment today.